Myeloproliferative neoplasms – blurring the lines between cancer and chronic inflammatory disorder - Soyfer, Eli M.; Fleischman, Angela G. (Frontiers in Oncology, 2023)
Myeloproliferative Neoplasm (MPN) is a group of chronic blood cancers that arise from a hematopoietic stem cell (HSC) clone with somatic mutations causing constitutive activation of myeloid cytokine receptor signaling. In addition to elevated blood cell counts, MPN typically presents with increased inflammatory signaling and inflammation symptoms. Therefore, while being a clonally derived neoplasm, MPN has much in common with chronic non-cancerous inflammatory conditions, such as rheumatoid arthritis, lupus, and many more. MPN and chronic inflammatory disease (CID) share similar chronicity, symptoms, dependency on the adaptive immune system, environmental triggers, and treatments. Overall, we will highlight the similarities between an MPN and CID. We highlight that while MPN is classified as a cancer, its behavior is more aligned to that of a chronic inflammatory disease. We propose that MPN should inhabit a more fluid/spectrum between auto-inflammatory disease and cancer.